2023
DOI: 10.3390/su151310251
|View full text |Cite
|
Sign up to set email alerts
|

Risk-Based Approach in the Implementation of Integrated Management Systems: A Systematic Literature Review

Abstract: The risk-based approach is one of the keys used in the implementation of management systems using requirements from the management standards. If the management systems are implemented separately, the risks are evaluated from only one perspective, but when two or more systems are integrated, the approach must take into account the synergetic effects of the risks due to system integration. The paper aims to highlight the specific risks encountered when implementing management systems in organizations, underlinin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 165 publications
0
3
0
Order By: Relevance
“…This will affects export performance positively. Similarly, Ispas et al (2023) also highlight the same interpretation in study. The study showed that if a firm adopts to the IMS standards, it improves their relations with the supplier (Kazi Humayra Shams et al, 2023).…”
Section: The Effect Of Ims Adoption On the Export Performance Of Firmssupporting
confidence: 82%
“…This will affects export performance positively. Similarly, Ispas et al (2023) also highlight the same interpretation in study. The study showed that if a firm adopts to the IMS standards, it improves their relations with the supplier (Kazi Humayra Shams et al, 2023).…”
Section: The Effect Of Ims Adoption On the Export Performance Of Firmssupporting
confidence: 82%
“…Overall, when we incorporate risk management and risk-based thinking into food ethics we allow for a systemic approach to identifying, assessing, and addressing ethical concerns in food production and consumption described by Ispas et al [168]. If we proactively manage risks and seize opportunities that align with ethical values, we will allow the food industry to uphold its commitment to ethical standards and contribute to a more sustainable and responsible food system.…”
Section: Assess E Ectiveness and Compliancementioning
confidence: 99%
“…Crear una cultura preventiva en los trabajadores, debido a la labor que desempeñan Payá et al (41) (2020) Cualitativa La presencia de autoridades especializadas, no asegura el fomento de medidas preventivas.…”
Section: Cuantitativounclassified
“…Para la eficiente cultura preventiva en materia de riesgos laborales a nivel psicosocial, es importante mantener una política que se base en la representación especializada de planes de prevención, esto provoca que, según Payá et al (41) , los procedimientos tengan un carácter relacional. Deben existir delegados de prevención lo cual se vincula con la generación de planes y procedimientos que permiten evitar el estrés laboral, de igual manera las "amenazas, insultos o agresiones".…”
Section: Cultura Preventivaunclassified